Kesiapan Akademic Dan Persepsi Untuk Implementasi Pendidikan Interprofessional - Andi Suswani; Risnah; A.Nurlaela Amin; Haerani (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2021)
Background: Interprofessional Education (IPE) is a collaborative practice between two or more health professions that learn each other's role of a profession that aims to improve collaboration skills and quality of healthcare. This research aims to analyze the perception and readiness of students and lecturers about IPE for the financial improvement of health education. Method: This type of research is descriptive analysis with a proportional approach. The qualitative method of Triangulation design is used to get more information about the readiness and perception of lecturers and students in the implementation of IPE. Sampling techniques are purposive sampling techniques and snowball sampling. The number of samples was 26, consisting of a 16-person lecturer and 9-man students. Result: The results showed that students have readiness in IPE implementation because students have high confidence in their ability to cooperate with other health professions. Unlike the lecturers, which states that most are less prepared in the IPE implementation. This difference is due to most of the lecturers having never participated in the socialization/training/workshop about IPE. Students have a good perception of IPE implementation because they consider that learning along with other health professions can teach how to study and work in a team, hone communication skills, understand the task and Responsibilities according to their profession. Lecturers have a good perception in the implementation of IPE because they have understood that collaboration with other health professions can improve the quality of health services but still need implementation strategy of the main preparation activities Institutions. Conclusion: Most lecturers and students are not ready in the implementation of IPE and most of the lecturers and students are well-perceptual to the IPE implementation.